True blues : the contentious transformation of the Democratic Party - Hilton, Adam, 1984- (American governance., 2021)
Tracing the rise of the advocacy party from the fall of the New Deal order through the presidency of Barack Obama, True Blues explains how and why the Democratic Party has come to its current crossroads and suggests a bold new perspective for comprehending the dynamics driving American party politics more broadly.